Croatian Coastal Festivals and the Construction of the Mediterranean - Škrbić Alempijević, Nevena (Array, 2010)
The focus of this paper is on festivals viewed as arenas in which cultural identities are built and reasserted. References to tradition and the past play a mayor role in this process. The authors analyze four thematically different festivals taking place along the Croatian Adriatic coast: the Festival of Dalmatian "Klapa" Singers in Omiš, the Rab Fiesta, the Dubrovnik Summer Festival and the Split Summer Festival. They are approached as ways of rediscovering and constructing Mediterranean imagery on stage.